2009
DOI: 10.1007/s00436-009-1603-x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of temperature on the viability of Demodex folliculorum and Demodex brevis

Abstract: Demodex folliculorum and Demodex brevis are obligatory parasites of the pilosebaceous unit in humans and are cosmopolitan in terms of their distribution. This study was conducted to explore the effect of temperature on the viability of D. folliculorum and D. brevis. Both types of parasites were collected with the cellophane tape method, then randomly grouped and placed into separate moist cabinets. They were divided into 15 groups and exposed to experimental temperatures ranging from -15 degrees C to 60 degree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 4 publications
2
32
0
2
Order By: Relevance
“…The temperatures tested in this study were based on Zhao et al (2009), who studied the activity and viability of D. folliculorum and D. brevis at temperatures ranging from -15 to ?60°C. There it was found that both species move weakly below 16°C and survive shorter above 37°C.…”
Section: Discussionmentioning
confidence: 99%
“…The temperatures tested in this study were based on Zhao et al (2009), who studied the activity and viability of D. folliculorum and D. brevis at temperatures ranging from -15 to ?60°C. There it was found that both species move weakly below 16°C and survive shorter above 37°C.…”
Section: Discussionmentioning
confidence: 99%
“…Staphylococcus Epidermidis isolated from patients with rosacea secretes more proteins (of which a lipase) at 37° compared with 30° 55 . The motility of D increases with temperature: at 37°C, the mites are extraordinarily active, but have a shorter survival time 56 . Perhaps an optimal temperature favouring D copulation exists?…”
Section: Demodex and Its Major Pathogenic Mechanismsmentioning
confidence: 99%
“…With the pathogenicity of the mites parasitizing in animals like dog, goat, etc. and human being confirmed successively (Smith 1961;Sheahan and Gaafar 1970;Zhao et al 2010Zhao et al , 2011aZhao et al , b, 2012b, researchers have done some work in the ecology and cultivation of Demodex mites, as well as the therapy of demodicidosis (Heine et al 2005;Xhaxhiu et al 2009;Zhao et al 2009;Fourie et al 2009). It has been reported that the pathogenicity of Demodex is related to population.…”
Section: Discussionmentioning
confidence: 93%